Socialization of the Importance of Early Diabetes Mellitus Prevention using Poster Media for Young Tenants of Boarding House in Tembalang Sub-District, Semarang - Aulia Meirizka Saputra; Fanda Indriyani; Dian Purwo Jatinging Putri; Ainutajriani Ainutajriani; Stalis Norma Ethica (Universitas Mathla'ul Anwar Banten, 2021)
Diabetes mellitus (DM) is among non-communicable diseases causing high number of morbidity and mortality in developing countries including Indonesia. Clinically, DM is a condition when blood sugar (glucose) levels exceed 126 mg/ dl in a fasting state and exceed 200 mg / dl in a non-fasting state. Public understanding is still relatively low about possibility of early DM in young people. Teens could be susceptible to DM, especially when they have poor diet and sedentary lifestyle Efforts to prevent early DM among teenagers have been done through Community Health Development Program (Program Pembangunan Kesehatan Masyarakat, PPKM) using poster as socialization media to the young tenants of boarding house at Sambiroto Residence, Tembalang Sub-District, Semarang, Central Java, Indonesia. The aim was to increase the teenagers' awareness of knowing the risks and clinical symptoms of diabetes mellitus. It is also to add insight on how to prevent DM disease at a young age. Participatory approaches and counseling have been carried out in the community service activities through the poster media, as well as the delivery of questionnaires prior- and post- counseling. The results of the questionnaire analysis showed that the counseling program using poster as media could improve awareness about DM among boarding house young tenants in Sambiroto Residence, Tembalang, Semarang City.